2011
DOI: 10.2298/hemind110902071d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and swelling behavior of polyurethane networks based on hyperbranched polymer

Abstract: A series of six polyurethane (PU) networks was synthesized from BoltornR hydroxy-functional hyperbranched polyester (HBP) of the second pseudo generation as a crosslinking agent, α,ω- dihydroxy-(ethylene oxide-poly(dimethylsiloxane)-ethylene oxide) (EO-PDMS-EO) and 4,4’- methylenediphenyl diisocyanate, by a two-step polymerization in solution. Each sample of the prepared PUs had different EO-PDMS-EO content. The chemical structure of the synthesized networks was analyzed by FTIR spectroscopy. The influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
3
16
0
3
Order By: Relevance
“…The peak at 1120 cm −1 stem from OCH 3 vibrations . As for Cur/PU nanocomposites (curve 2), we could detect the same peaks as in curcumin sample shifted with a peak at 3400 cm −1 could be assigned to OH stretching vibrations whereas the peaks at 2940 and 2854 cm −1 belong to sp 2 and sp 3 CH stretching vibrations . The peaks at 1730, 1701, 1614, and 1529 cm −1 are stemming from carbonyl groups.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The peak at 1120 cm −1 stem from OCH 3 vibrations . As for Cur/PU nanocomposites (curve 2), we could detect the same peaks as in curcumin sample shifted with a peak at 3400 cm −1 could be assigned to OH stretching vibrations whereas the peaks at 2940 and 2854 cm −1 belong to sp 2 and sp 3 CH stretching vibrations . The peaks at 1730, 1701, 1614, and 1529 cm −1 are stemming from carbonyl groups.…”
Section: Resultssupporting
confidence: 61%
“…Values of three parallel swelling experiments for each sample are averaged. The swelling degree was calculated by gravimetric method …”
Section: Methodsmentioning
confidence: 99%
“…The large number of terminal hydroxyl groups present in Boltorn ® HBPs enables fast formation of networks that have good mechanical properties, as well as good resistance to chemicals [11][12][13][14], while the presence of PDMS contributes to the good thermal and surface properties, and to elasticity of the highly crosslinked materials. In our previous studies, we have investigated the influence of the content of !,"-dihydroxyethoxy propyl-poly(dimethylsiloxane) (EO-PDMS) and type of HBPs on the swelling behavior, morphological, thermal and thermomechanical properties of PU networks [15][16][17][18][19][20][21]. These results confirmed that physical and thermal properties are related to the crosslinking density, hydrogen bonding interactions, microphase separation and content of EO-PDMS soft segment.…”
supporting
confidence: 55%
“…Catalyst concentration was kept at 0.02 wt% [25][26][27]. The details for the synthesis of similar PU networks are given in our previously published papers [16][17][18][19][20][21]. Compositions of the synthesized PUs and weights of the reactants used for the synthesis of PUs are presented in Table 1.…”
Section: Synthesis Of Pu Films Based On Pdmsmentioning
confidence: 99%
“…Measured values from three parallel swelling experiments were averaged. Gravimetric method has been used to calculate the swelling degree [39].…”
Section: Characterization Of Hcqds/pdms Nanocompositesmentioning
confidence: 99%